A techno-economic review of multi effect desalination systems integrated with different solar thermal sources. (25th February 2021) - Baniasad Askari, Ighball; Ameri, Mehran
Highlights: The solar/multi effect desalination technology is not still economically justified. The unit cost of fresh water using this technology ranges from 1.4$/ m 3 to 3.6$/ m 3 . Localization of the solar thermal technology industry reduces the freshwater cost. More attentions should be paid to power/water production by Solar Tower technology. Future research must focus on decreasing the solar collectors' capital costs. Abstract: The scarcity of fresh water resources and the need for additional water supplies is already critical in many arid regions of the world and will be increasingly important in the future. The solar thermal/Multi Effect Desalination (MED) is a candidate to tackle water scarcity. A comprehensive review of the technical and economic aspects of the technology and the state-of-the-art investigations in terms of integration of various MED configurations with different solar thermal sources was provided. Based on the results, the unit cost of the fresh water varies depending on the solar thermal technology and cost, solar radiation level, water production rate, seawater temperature and salinity. Based on the review, the integration of the MED with low temperature (60 °C–95 °C), medium temperature (165 °C–200 °C) and high temperature (370 °C–530 °C) solar collectors leads to water production costs of 2$/ m 3 –3.6$/ m 3, 1.4$/ m 3 –3.1$/ m 3 and 1.8$/ m 3 −2.2$/ m 3, respectively, with a payback period of 4 to 16 years. The directions for the future research include localization of the solar collector industry, the MED brine management, the improvement of the MED and solar collector thermal efficiencies as well as the integration schemes. Useful information is provided to choose the most appropriate combinations of solar/MED technology for small or large applications.